The Role of Arbitration and Mediation in Resolving Disputes Arising from International Business Transactions - Lim, Grace Natalie (Universitas Ibn Khaldun Bogor, 2025)
The resolution of disputes in international business transactions is a crucial aspect of maintaining stability and continuity in cross-border trade relations. Arbitration and mediation are the primary mechanisms frequently used due to their flexibility, efficiency, and neutrality compared to litigation in national courts. International arbitration provides legal certainty with binding decisions enforceable under the 1958 New York Convention, while mediation focuses on a compromise-based solution that preserves long-term business relationships. This article analyzes the effectiveness of both mechanisms in resolving international business disputes and examines the role of institutions such as the ICC (International Chamber of Commerce) and ICSID (International Centre for Settlement of Investment Disputes) in facilitating dispute resolution. Furthermore, this study highlights the challenges faced, including differences in legal systems, the enforcement of arbitration decisions, and the reluctance of parties to engage in mediation. The findings indicate that the choice between arbitration and mediation depends on the complexity of the dispute, the interests of the parties, and the need for legal certainty or negotiation flexibility. Therefore, a comprehensive understanding of arbitration and mediation is essential for international business actors to manage legal risks and ensure smooth cross-border transactions.